(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Objective Saliva, the oral biofluid protects, lubricates, and aids in mastication, speaking, and digestion. Salivary flow can be reduced as a result of a range of external factors and natural changes. Xerostomia frequently goes underreported and health care providers tend to disregard the condition while managing critical issues. Methodology The survey was conducted among 838 participants who were all health care providers. They were further sub grouped as dental practitioners, medical practitioners, dental post graduates and medical post graduates. The questionnaire included 30 questions under sections; knowledge of hyposalivation; awareness on the oral and systemic effects; and practices followed for management of the condition. Statistical analysis was carried out using SPSS software and the data was presented as percentages. Results On the whole 838 recorded responses were compared between dental (N =404) and medical care providers (N= 434 ). It could be established that both groups had almost similar responses, with dental professionals having somewhat superior understanding with respect to dental and periodontal impacts and medical respondents having slightly more knowledge of systemic effects of hyposalivation. Among postgraduates, Dental postgraduates perceived xerostomia to be self-reported, which was statistically significant (p < 0.05).Besides, there were notable differences among the treatment approaches. Conclusion The importance of appropriately managing xerostomia could be assessed by examining the knowledge and awareness of health care providers. Although there was little difference in perception between dental and medical professionals, there is a need to emphasize the management of this underappreciated clinical presentation.